REAKTUALISASI PUISI ANTIKORUPSI SEBAGAI SALAH SATU MEDIA KAMPANYE SOSIAL MASYARAKAT - Dewi Ambarwati (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2024)
The trident of corruption eradication can be done through prosecution, prevention, and education. To prevent corruption, the community can play a role through various media of counseling and education, one of which is poetry. Poetry has its characteristics as part of the arts, so through poetry, the community can provide anti-corruption messages that are easily remembered and understood by the readers. However, today, there are not many people who can utilize poetry as one of the media for anti-corruption social campaigns, and determine the stages of a tactical and targeted social campaign by utilizing poetry. Based on these problems, an activity focusing on improving skills in creating anti-corruption poetry is needed. The purpose of this activity is to increase the awareness and skills of poets and poetry makers in the context of anti-corruption education. The method used in this activity was discussion and practicing making poetry with an anti-corruption theme. The result of this activity was that the participants were able to understand and produce anti-corruption poetry as one of the social campaign media that can be addressed to a predetermined target group.